2022
DOI: 10.1002/ar.25117
|View full text |Cite
|
Sign up to set email alerts
|

Pure total flavonoids from citrus improve nonalcoholic steatohepatitis liver inflammatory responses by regulating the CCL2/CCR2‐PI3K‐Akt signal transduction pathway

Abstract: Background and AimNonalcoholic steatohepatitis (NASH) is a critical stage in the prognosis of nonalcoholic fatty liver disease (NAFLD). Pure total flavonoids from circus (PTFC) play essential roles in the improvement of NASH symptoms, but the underlying regulatory mechanism remains elusive. Our previous high‐throughput omics screening results indicate that the CCL2/CCR2‐PI3K‐Akt signaling pathway is a key pathway that regulates the liver inflammatory response. PTFC may regulate the CCL2/CCR2‐PI3K‐Akt signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…They identified potential biomarkers for differential diagnosis by detecting and analyzing T lymphocytes and the HMGB1/PTEN/PI3K signaling pathway in the blood of healthy individuals and patients with chronic hepatitis B associated with LDSDS and SGDHS (Jiang et al, 2023). In another study using a mouse model of nonalcoholic steatohepatitis, Wu et al (2023) explored the effects of pure total flavonoids from citrus (PTFC) intervention, and found that the CCL2/CCR2‐PI3K‐Akt signaling pathway positively participated in PTFC‐induced alleviation of hepatic inflammation. Moreover, Deng and his group explored the mechanism of anti‐hepatic fibrosis of Chinese herbal components on lipopolysaccharide‐induced macrophage exosomes co‐cultured withJS1 cells (Deng et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…They identified potential biomarkers for differential diagnosis by detecting and analyzing T lymphocytes and the HMGB1/PTEN/PI3K signaling pathway in the blood of healthy individuals and patients with chronic hepatitis B associated with LDSDS and SGDHS (Jiang et al, 2023). In another study using a mouse model of nonalcoholic steatohepatitis, Wu et al (2023) explored the effects of pure total flavonoids from citrus (PTFC) intervention, and found that the CCL2/CCR2‐PI3K‐Akt signaling pathway positively participated in PTFC‐induced alleviation of hepatic inflammation. Moreover, Deng and his group explored the mechanism of anti‐hepatic fibrosis of Chinese herbal components on lipopolysaccharide‐induced macrophage exosomes co‐cultured withJS1 cells (Deng et al, 2023).…”
Section: Introductionmentioning
confidence: 99%